2018
DOI: 10.1136/bmjopen-2017-018166
|View full text |Cite
|
Sign up to set email alerts
|

Impact of red and processed meat and fibre intake on treatment outcomes among patients with chronic inflammatory diseases: protocol for a prospective cohort study of prognostic factors and personalised medicine

Abstract: IntroductionChronic inflammatory diseases (CIDs) are frequently treated with biological medications, specifically tumour necrosis factor inhibitors (TNFi)). These medications inhibit the pro-inflammatory molecule TNF alpha, which has been strongly implicated in the aetiology of these diseases. Up to one-third of patients do not, however, respond to biologics, and lifestyle factors are assumed to affect treatment outcomes. Little is known about the effects of dietary lifestyle as a prognostic factor that may en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 122 publications
0
37
0
Order By: Relevance
“…The detailed aetiology of the IBDs remains unknown, but experimental and observational studies such as meta-analyses and cohort-and case-control studies suggest that CD and UC have both genetic and environmental predisposing factors (16)(17)(18)(19)(20). Use of nonsteroidal anti-in ammatory drugs (NSAIDs)(21), use of hormone replacement therapy (HRT) (22), obesity (23,24) and dietary factors such as red meat (25) and alcohol (26,27) have been suggested as risk factors for intestinal in ammation and onset of IBD, whilst it is suggested that intake of dietary bre (16,28) and fermented dairy products (29,30) may play a preventative role. Interestingly smoking, has been associated with a higher risk of CD, whilst is seen as being protective for UC (31,32).…”
Section: Chronic In Ammatory Bowel Diseasesmentioning
confidence: 99%
“…The detailed aetiology of the IBDs remains unknown, but experimental and observational studies such as meta-analyses and cohort-and case-control studies suggest that CD and UC have both genetic and environmental predisposing factors (16)(17)(18)(19)(20). Use of nonsteroidal anti-in ammatory drugs (NSAIDs)(21), use of hormone replacement therapy (HRT) (22), obesity (23,24) and dietary factors such as red meat (25) and alcohol (26,27) have been suggested as risk factors for intestinal in ammation and onset of IBD, whilst it is suggested that intake of dietary bre (16,28) and fermented dairy products (29,30) may play a preventative role. Interestingly smoking, has been associated with a higher risk of CD, whilst is seen as being protective for UC (31,32).…”
Section: Chronic In Ammatory Bowel Diseasesmentioning
confidence: 99%
“…The detailed aetiology of the IBDs remains unknown, but experimental and observational studies such as meta-analyses and cohort-and case-control studies suggest that CD and UC have both genetic and environmental predisposing factors (16)(17)(18)(19)(20). Use of nonsteroidal anti-inflammatory drugs (NSAIDs) (21), use of hormone replacement therapy (HRT) (22), obesity (23,24) and dietary factors such as red meat (25) and alcohol (26,27) have been suggested as risk factors for intestinal inflammation and IBD onset, while a preventative role of intake of dietary fibre (16,28) and fermented dairy products (29,30) has been suggested. Smoking, however, has been associated with a higher risk of CD, while being protective for UC (31,32).…”
Section: Chronic Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…We cannot exclude the possibilities of harmful effects of food additives on IBD, although the relevant human data are deficient. Several prospective cohorts have been conducted to figure out the underlying relationship.…”
Section: Diet In the Pathogenesis Of Ibdmentioning
confidence: 99%
“…29 We cannot exclude the possibilities of harmful effects of food additives on IBD, although the relevant human data are deficient. Several prospective cohorts 22,30 have been conducted to figure out the underlying relationship. 31 But such a protective effect was only found in those having a higher intake of fibers derived from fruits rather than that from whole grain, legumes and cereals.…”
Section: Food Additivesmentioning
confidence: 99%